The great imitator: Tuberculosis with lymphadenopathy and splenomegaly - Hall, Ashton D. (2024)
Tuberculosis (TB) is a leading infectious killer worldwide. Over two-thirds of new TB diagnoses in the United States occur among first-generation immigrants, especially within a year of migration. Hodgkin lymphoma (HL) accounts for a minority of lymphoma cases but presents similarly to disseminated or extrapulmonary TB. Clinical overlap between TB and HL increases patient risk of misdiagnosis. Concomitant presentation of both diseases is not uncommon but infrequently reported. We present a case of isoniazid-resistant TB with progressively worsening lymphadenopathy and splenomegaly despite appropriate TB treatment. The patient was diagnosed with HL following PET/CT and axillary lymph node biopsy.